2017
DOI: 10.1071/ah16038
|View full text |Cite
|
Sign up to set email alerts
|

Social participation as an indicator of successful aging: an overview of concepts and their associations with health

Abstract: Objectives. Social participation has generated a wealth of research in gerontology, but the concept suffers from a lack of conceptual clarity that renders it difficult to define and measure. This means that research on social participation is difficult to compare directly. The aim of the present study was to draw the literature on social participation in older adults together to inform health services researchers seeking to investigate social participation as an indicator of successful aging.Methods. A narrati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

11
219
0
11

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 258 publications
(262 citation statements)
references
References 80 publications
11
219
0
11
Order By: Relevance
“…Thus, the region‐wide strategies aimed at tackling these regional challenges will remain indispensable. The improvement of population health status and enhancement of social participation are important for the successful ageing of the older adults (ActiveAge, , Douglas, Georgiou, & Westbrook, ). As suggested by previous studies, the focus should not only be on the specific physical needs of the older adults but also on strengthening the older adults’ connection with their community (Douglas et al., ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, the region‐wide strategies aimed at tackling these regional challenges will remain indispensable. The improvement of population health status and enhancement of social participation are important for the successful ageing of the older adults (ActiveAge, , Douglas, Georgiou, & Westbrook, ). As suggested by previous studies, the focus should not only be on the specific physical needs of the older adults but also on strengthening the older adults’ connection with their community (Douglas et al., ).…”
Section: Discussionmentioning
confidence: 99%
“…Social participation is defined in our study as participating in the labour market, informal care or volunteer work. We recognise, however, that social participation could also be viewed as a broader concept (Douglas et al., ) and combinations of social activities should be considered in future studies. Further research is also needed to study the social participation rates and their determinants within and across the municipalities in the Netherlands.…”
Section: Discussionmentioning
confidence: 99%
“…While Delli-Colli, Dubuc, HĂ©bert, Lestage, and Dubois (2013) found that identifying older adults' psychosocial needs can influence a social worker's decision to tailor services accordingly, adoption of psychosocial assessments has not yet been integrated into standard practice within community care. This is rather surprising given how social engagement and community participation is recognised as an indicator of successful ageing (Douglas, Georgiou, & Westbrook, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have reported that social participation decreases stress levels . In addition, social participation might prevent dementia onset and functional decline; and social participation greatly improves quality of life in older people …”
Section: Introductionmentioning
confidence: 98%
“…1 In addition, social participation might prevent dementia onset and functional decline; [2][3][4] and social participation greatly improves quality of life in older people. 5 According to a Japanese national survey, a substantial number of individuals who are currently non-participants in social groups are willing to engage in social groups. 6 To promote engagement in social group activities, it is necessary to identify factors that influence initiation of participation and develop interventions targeted at these factors.…”
Section: Introductionmentioning
confidence: 99%